A Diagnostic Study of 150 Cases of Gliomas Based on Immunohistochemical Profile (Medical Forum Monthly, 2022)
Objective: To present an overview of the relative frequency of gliomas in the light of expression of biomarkers relevant to the tumor grade.Study Design: Descriptive studyPlace and Duration of Study: This study was conducted at the Department of Pathology, Gulab Devi Teaching Hospital Lahore from February 2018 to December 2020.Materials and Methods: 150 glioma samples were obtained from the pathology department of Lahore General Hospital by convenience sampling techniqueto be evaluated histologically for grading of the types of a tumor subsequent to hematoxylin & eosin staining. For tumor markers, immunohistochemistry was performed to assess the levels of glial fibrillary acidic protein (GFAP), nestin, and vimentin. The basic and immunostained sections were then assessed by three pathologists deprived of the pathological and clinical data of patients` parameters in a blinded manner. The outcomes of staining were semi-quantitatively scored. The data of incidence rates by histologic type, age, and gender was collected.Results: The mean age of patients with gliomas was 21.71±16.9. The benign astrocytoma was the most frequent glioma making 52% of all the tumors. The males were on an average 59.34% and the females were 40.66%. The expression level of GFAP staining was considerably lower in high-grade glioma tissues as compared to low-grade glioma tissues. The majority of gliomas revealed moderation expression of nestin around 53.4%. The mean score of vimentin was 8.3 indicating its high expression for the grade IV gliomas.Conclusion: The expression of biomarkers for gliomas correlated with the grade of the tumor. The mean age revealed gliomas occurring in the younger age group without a major difference in gender distribution.